ANALISIS LIKUIDITAS HARGA SAHAM PERUSAHAAN KONSTRUKSI YANG LISTING DI BURSA EFEK JAKARTA - Windi Irmayani (Universitas Bina Sarana Informatika, 2013)
Liquidity is very closely related to the availability of cash , which is cash available to support the company's policy to distribute dividends to shareholders, repay loans, pay interest on the loan, the operations of the company and make new investments. Where this will be a stimulant for investors to buy shares of a company. Which will cause a rise in the company's stock price. This study to determine the effect of liquidity on stock prices of construction companies listed on the JSE. To achieve these objectives, the program used E views 4.1 applications to determine regression equations and correlation. The data used is downloaded from www.jsx.co.id data as well as data from PT Bumi Capital Indonesia. In connection with the results of the statistical test F test results 2.757036 F count is less than F table 3.37. That is, the simultaneous liquidity ratio (current ratio and cash ratio) had no significant effect on stock prices.Key words: Liquidity, Investments, Stock.